Reliability of Power supply study aid - Nikitin specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences; Saigash Specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences; Sivkov Specialist in the field of electric power engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences; Rakhmatullin specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of Sciences (Tomsk Polytechnic University Publishing House, 2021)
This book provides state of the art tools for analyzing power supply system's reliability. This material will be useful for those who need to use these tools as well as those who want to do further research. They will be able to use this knowledge to make trade-offs between reliability, cost, environmental issues and other factors as needed. The book is intended for Master in the direction of 13.04.02 "Electric Power and Electrical Engineering" (Program name: "Electric Power Generation and Transportation"), studying reliability of power supply. It may be of interest to master and postgraduate students of department of electric power and electrical engineering.